Effects of aerobic exercise on the blood pressure, oxidative stress and eNOS gene polymorphism in pre-hypertensive older people - Zago, Anderson Saranz; Silveira, Leonardo Reis; Kokubun, Eduardo [UNESP] (Springer, 2010)
The polymorphisms of endothelial nitric oxide synthase (eNOS) are associated with reduced eNOS activity. Aerobic exercise training (AEX) may influence resting nitric oxide (NO) production, oxidative stress and blood pressure. The purpose of this study was to investigate the effect of AEX on the relationship among blood pressure, eNOS gene polymorphism and oxidative stress in pre-hypertensive older people. 118 pre-hypertensive subjects (59 +/- A 6 years) had blood samples collected after a 12 h overnight fast for assessing plasma NO metabolites (NOx) assays, thiobarbituric acid reactive substances (T-BARS) and superoxide dismutase activity (ecSOD). eNOS polymorphism (T-786C and G-894T) was done by standard PCR methods. All people were divided according to the genotype results (G1: TT/GG, G2: TT/GT + TT, G3: TC + CC/GG, G4: TC + CC/GT + TT). All parameters were measured before and after 6 months of AEX (70% of VO(2 max)). At baseline, no difference was found in systolic and diastolic blood pressure, ecSOD and T-BARS activity. Plasma NOx levels were significantly different between G1 (19 +/- A 1 mu M) and G4 (14.2 +/- A 0.6 mu M) and between G2 (20.1 +/- A 1.7 mu M) and G4 (14.2 +/- A 0.6 mu M). Therefore, reduced NOx concentration in G4 group occurred only when the polymorphisms were associated, suggesting that these results are more related to genetic factors than NO-scavenging effect. After AEX, the G4 increased NOx values (17.2 +/- A 1.2 mu M) and decreased blood pressure. G1, G3 and G4 decreased T-BARS levels. These results suggest the AEX can modulate the NOx concentration, eNOS activity and the relationship among eNOS gene polymorphism, oxidative stress and blood pressure especially in C (T-786C) and T (G-894T) allele carriers.
Keywords: Nitric oxide; Physical exercise; eNOS polymorphism; Blood pressure; Oxidative stress; Elderly